About the differences between communication networks and cognitive networks. Contribution to Research of Bibliometric methods in Information Science - Pečarić, Đilda (Array, 2011)
In this paper we advocate thesis that cohesion and coherence of scientific field should be conceptual framework, i.e. criterion for the research of scientific development. With such an approach we can research scientific development realized through social networks, institutional networks, communicational networks and cognitive networks. All these forms of scientific collaboration, i.e. all these networks can influence the structure and dynamics of the development of (information) sciences. In that context, bibliometric data used as indicators of cohesion and coherence of information science are not only quantitative indicators, but could also be used as quantitative data of qualitative indicators that we could define by new conceptual framework. We believe that it is possible to advocate following hypothesis: a) two scientific communities can use (generate) two different communication networks (that can be identified by co-citation analysis, that is, clusters of most cited authors) ; b) two scientific communities can generate same or similar cognitive networks (that can be identified by co-word analysis). These postulate the difference between communication and cognitive networks. That means that “knowledge maps” and “intellectual structure” as the product of bibliometric analysis from 1980s on are not precise enough today.